SHP2 Regulates the Osteogenic Fate of Growth Plate Hypertrophic Chondrocytes - Wang, Lijun; Huang, Jiahui; Moore, Douglas C.; Zuo, Chunlin; Wu, Qian; Xie, Liqin; von der Mark, Klaus; Yuan, Xin; Chen, Di; Warman, Matthew L.; Ehrlich, Michael G.; Yang, Wentian (Scientific Reports, 2017)
Transdifferentiation of hypertrophic chondrocytes into bone-forming osteoblasts has been reported, yet the underlying molecular mechanism remains incompletely understood. SHP2 is an ubiquitously expressed cytoplasmic protein tyrosine phosphatase. SHP2 loss-of-function mutations in chondroid cells are linked to metachondromatosis in humans and mice, suggesting a crucial role for SHP2 in the skeleton. However, the specific role of SHP2 in skeletal cells has not been elucidated. To approach this question, we ablated SHP2 in collagen 2α1(Col2α1)-Cre- and collagen 10α1(Col10α1)-Cre-expressing cells, predominantly proliferating and hypertrophic chondrocytes, using "Cre-loxP"-mediated gene excision. Mice lacking SHP2 in Col2α1-Cre-expressing cells die at mid-gestation. Postnatal SHP2 ablation in the same cell population caused dwarfism, chondrodysplasia and exostoses. In contrast, mice in which SHP2 was ablated in the Col10α1-Cre-expressing cells appeared normal but were osteopenic. Further mechanistic studies revealed that SHP2 exerted its influence partly by regulating the abundance of SOX9 in chondrocytes. Elevated and sustained SOX9 in SHP2-deficient hypertrophic chondrocytes impaired their differentiation to osteoblasts and impaired endochondral ossification. Our study uncovered an important role of SHP2 in bone development and cartilage homeostasis by influencing the osteogenic differentiation of hypertrophic chondrocytes and provided insight into the pathogenesis and potential treatment of skeletal diseases, such as osteopenia and osteoporosis.
EVALuna2:35508